MOLECULAR DETECTION OF Toxoplasma gondii IN CHICKEN LICE (Menacanthus stramineus) - Sura E. Ahmed; Nadia K. Thamar; Rasha M. Othman (Basrah Journal of Veterinary Research)
The current study was carried out to demonstrate the ability of chicken liceMenacanthus stramineus to transmit Toxoplasma gondii by using PCR technique. Theblood was collected from the jugular vein of 85 chickens infested with ectoparasitesto investigate the existence of Toxoplasma gondii by latex agglutination test. Theresults showed that 42 (49.41%) of chicken were infected with lice, lice samples ofMenacanthus stramineus were collected from chickens infected with T.gondii forPCR investigation to confirm the presence of T.gondii in lice tissues and the resultswere revealed the presence of T. gondii B1 genein 18(42.85 %) samples.